Restriç\~oes comerciais às exportaç\~oes de produtos siderúrgicos no Mercosul - Márcio de Oliveira Júnior (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– The main aim of this paper is to identify and to analyze the presence of Non Tariff Barriers (NTBs) in the trade of steel products among Brazil and the other three Mercosur's member countries. The NTBs were identified through interviews with Brazilian companies and through questionaries sent to Brazilian firms that export over one hundred thousand dollars yearly. Brazilian companies did not identify any NTB imposed by Paraguay or Uruguay. Argentina, the second largest steel producer in Mercosur, is the only trade partner that uses NTBs when trading steel products with Brazil. This happens because Argentina, in order to avoid a sharp drop in its domestic production, had to protect its firms from external competition after the drop in its internal demand. The alternative strategy to avoid reducing the production would be to raise exports. This became difficult since world prices and demand fell after the Asian Crisis and since Argentine prices are not competitive when compared to its Asian and Eastern European counterparts. The main NTBs imposed by Argentina identified by Brazilian companies are of four types: a) safety and industrial standards and regulations; b) antidumping duties; c) discriminatory bilateral agreements; and customs clearance procedures.
Keywords: 330; Außenhandel; Nichttarifäre Handelshemmnisse; Brasilien; Mercosur-Staaten; Stahlprodukt